In-shoe plantar pressure measurement-influence of insole placement on selected parameters during running - Mally, F.; Hofstätter, O.; Eckelt, M. (Proceedings, 2020)
While it is assumed that pressure-sensing insoles are usually placed directly below the foot and on top of the shoes` standard insoles, nearly no previously published study actually describes the procedure, which leaves a slight uncertainty. Therefore, the aim of this study was to evaluate whether the placement has an influence on selected parameters or not. Five healthy participants took part in the measurements and ran on a treadmill at a running velocity of 10 km/h with three different running shoes. Plantar pressure was measured using pressure-sensing insoles, which were once placed on top and once below the shoes` standard insoles. Selected parameters were the maximum and mean pressure and the range of the center of pressure (COP) in anterior-posterior and medial-lateral directions. The results indicate that maximum and mean pressure decrease when the pressure-sensing insole lies below the shoe`s insole and the medial-lateral COP is the least effected parameter.